(untitled) (Bangladesh Journal of Medical Microbiology, 2026)
Background: Dengue virus (DENV) remains the most prevalent arbovirus globally, with rising incidence in tropical and subtropical regions. Its expanding geographical distribution and increasing disease severity highlight the need for early and accurate diagnosis. Rapid detection during the febrile phase is crucial to guide clinical management and prevent complications. While real-time reverse transcription polymerase chain reaction (RT-qPCR) is the gold standard for molecular detection, its limited availability in resource-constrained settings necessitates alternative methods. Objective: This study was evaluated the diagnostic performance of reverse transcription loop-mediated isothermal amplification (RT-LAMP) for DENV serotyping, compared with RT-qPCR. Methodology: This cross-sectional study was conducted in the Department of Microbiology at Chittagong Medical College, Bangladesh, from July 2023 to June 2024. Two hundred patients with clinically suspected dengue were recruited. Initial screening used an immunochromatographic test (ICT) for NS1 antigen; NS1-negative cases were further tested for anti-dengue IgM and IgG antibodies. Samples positive by NS1, IgM, or both were subjected to RT-qPCR and RT-LAMP for DENV serotyping. RT-qPCR served as the reference standard. Results: Of 200 suspected cases, 142 were ICT-positive. RT-qPCR confirmed DENV in 138 samples, while RT-LAMP detected 136 of these. Two RT-qPCR-positive samples were missed by RT-LAMP, and four were negative by both methods. RT-LAMP showed a sensitivity of 98.55%, specificity of 100%, positive predictive value of 100%, negative predictive value of 66.67%, and diagnostic accuracy of 98.59%. Receiver operating characteristic analysis showed an area under the curve (AUC) of 0.993 (95% CI: 0.980–1.000; p = 0.001), indicating excellent diagnostic capability. Conclusion: RT-LAMP offers a rapid, affordable, and reliable alternative to RT-qPCR for early DENV detection and serotyping. Its simplicity and minimal equipment requirements make it especially valuable in dengue-endemic and resource-limited settings, as well as during outbreaks. Bangladesh Journal of Medical Microbiology, July 2025;19 (2):100-106